Three-Enzyme Cascade Catalyzes Conversion of Auramycinone to Resomycin in Chartreusin Biosynthesis - Niemczura, Magdalena; Nuutila, Aleksi; Wang, Rongbin; Rauhanen, Katariina; Nybo, S. Eric; Metsä-Ketelä, Mikko (American Chemical Society (ACS), 2025)
Chartreusin is a potent antiproliferative agent that contains a unique aromatic pentacyclic bislactone carbon scaffold. The biosynthesis of type II polyketide aglycone has been extensively investigated and shown to proceed through a tetracyclic anthracycline intermediate. The last remaining unknown steps are the conversion of auramycinone to resomycin C. Here we have discovered three enzymes that play crucial roles in two mechanistically distinct dehydration reactions. We show that ChaX is an NAD(P)H-dependent auramycinone quinone reductase that allows the cyclase-like ChaU to catalyze the formation of 9,10-dehydroauramycinone via a carbanion intermediate. In contrast, the cyclase-like ChaJ, homologous to ChaU, is responsible for subsequent 7,8-dehydration via a canonical carbocation intermediate, yielding resomycin C. The results were confirmed via assembly of the biosynthetic pathway for production of resomycin C in Streptomyces coelicolor M1152 Delta matAB. The work expands the catalytic repertoire of the SnoaL protein family, which has previously been associated with anthracycline fourth-ring cyclization and two-component 1-hydroxylation.